Financial wealth shocks and health - Declan French (Queen's University Belfast, Queen's Management School, 2021)
A number of studies have associated stock market movements with health-related outcomes arguing that the effect is due to psychological distress and is immediate. In this paper, we examine this relationship for cumulative shocks to the financial wealth of American retirees using the allostatic load model of pathways from stress to poor health. Wealth shocks are identified from Health and Retirement Study reports of stock ownership along with significant negative discontinuities in high-frequency S&P500 index data. We find that a one standard deviation change in cumulative shocks over a year changes the probability of high blood pressure by 10.2% and the cholesterol ratio by 7.4% of average values for those whose wealth is all in shares. Our findings imply older stock market investors should take account of welfare loss due to stress-related health conditions in managing their portfolio risk.
Keywords: 330; shock; jump; allostatic load; stock market; health